Learning Outcomes of Civil Engineering Students in PBL Based on Building Information Modeling - Ma, Jianhua; Tao, Yaping (International Journal of Emerging Technologies in Learning (iJET), 2023)
Abstract—The new technology called building information modeling (BIM) derived in China’s construction industry in the general background of information era, as well as construction of intelligent buildings and smart cities, requires many university students majoring in Civil Engineering who are skilled in BIM technology. Characterized by online learning at any time, free and diversified learning modes, and ubiquitous learning, project-based BIM teaching can effectively improve the learning outcomes of Civil Engineering majors. To explore such learning outcomes of these students from engineering technological universities from project-based BIM teaching, 240 junior students majoring in Civil Engineering from 4 universities in Henan Province, China were chosen as research objects (120 each for the control and 120 experimental groups). The effect of BIM teaching in improving learning outcomes was investigated through a 16-week teaching experiment of Design Theory for Concrete Structure. The experimental and control groups used the project-based BIM teaching and traditional teaching modes, respectively. On this basis, independent and paired sample T-tests were carried out to the experimental data. Research results showed that pre-test scores of the group and control groups have a normality trait, conforming to the preconditions of the teaching experiment. Pre- and post-test scores of the experimental group had evident differences. Post-test scores of the experimental group were 15.82 higher than the pre-test scores, and the difference had statistical significance (P < 0.001). Owing to BIM teaching, post-test performances of the control and experimental groups also had significantly statistical significance. Project-based BIM teaching can improve learning outcomes of university students majoring in Civil Engineering. Research conclusions have important references to build BIM teaching resource platform, solve scattered and insufficient BIM teaching resources, facilitate active learning of university students majoring in Civil Engineering, and improve teaching effect.